Developing an evaluation model for urban tourism competitiveness: combining community construction and community service to foster sustainable development of cities - Zhao, Yueyang; Shang, Wenxuan; Qin, Xiaochuan; Li, Kaicheng (Frontiers in Public Health, 2024)
This study presents an evaluation model for urban tourism competitiveness in China, developed within the context of the country's transition to a mature tourist destination. The study employs a multi-faceted methodology combining qualitative and quantitative approaches. The primary model used is an adapted version of Porter's Diamond Model, enhanced by integrating the IMD framework to cover social governance and environmental dimensions. A linear weighted evaluation method, incorporating the coefficient of variation entropy weight method, was used to derive comprehensive scores for sustainable development from 2008 to 2019. Key findings of the research indicate significant issues such as homogeneous competition, lack of strategic management, and insufficient service quality within the current urban tourism landscape. The study proposes solutions like creating boutique inland tourism routes, developing unique urban tourism brands, and enhancing regional cooperation and management practices. It also underscores the importance of balancing economic benefits with the preservation of cultural and natural assets for sustainable tourism development. The study provides a comprehensive evaluation model that incorporates community development and services, offering actionable insights for policymakers and planners.